Efficacy of low-level laser therapy as an adjunct to button anchored coronally advanced flap for gingival recession: A Doppler study - Jayakumar, Parvathee (J Indian Soc Periodontol, 2018)
Coverage of the exposed root is one of the periodontal plastic surgical procedures, which is one of the important periodontal treatment modalities. The introduction of innovation in new interdisciplinary treatment modalities has allowed us the use of orthodontic button in root coverage procedures using a coronally advanced flap (CAF) to provide the initial stabilization. This case report also evaluates the effectiveness of low-level laser therapy (LLLT) to detect the microvascular blood flow changes in the gingiva and alveolar mucosa where LLLT has been given after button-anchored CAF procedure during postoperative healing to detect blood flow changes of mucosa where LLLT was not given in other surgical sites. Three-month postoperative results showed that the LLLT used as an adjunct to CAF with the orthodontic button for stabilization is an effective surgical approach in the management of Miller's Class I recession defects.